Targeted design and analysis of microwave absorbing properties in iron-doped SiCN/Si3N4 composite ceramics. Issue 4 (15th February 2021) - Lin, Xiao; Gong, Hongyu; Zhang, Yujun; Zhang, Lu; Li, Ma; Wang, Shan; Adil, Saleem
Abstract: The SiCN(Fe)/Si3 N4 composite ceramics containing C, β-SiC and α-Fe were designed by impregnating polysilazane followed by pyrolysis at 1–5 times with porous silicon nitride matrix. After the heat treatment, these new phases gradually formed and filled in the pores of the matrix to form a large whole. They bond together to facilitate the formation of conductive networks, which can improve the storage and transport capacity of the charge, thus improving the dielectric properties of the material. In this way, the highest dielectric and magnetic loss tangent values were achieved as 0.49 and 0.29 after third and fourth cycles, respectively. The electromagnetic wave can be absorbed 80–90% in the range of 8–18 GHz with the thickness of 2 mm. The minimum reflectivity was −12.5 dB at 16 GHz with the thickness of 5 mm, showing >90% electromagnetic wave absorption at this frequency. Graphical abstract: Targeted Design of SiCN(Fe)/Si3 N4 Microwave Absorbing Composite Ceramics. Image 1